2019
DOI: 10.1177/1550147719837877
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive blood pressure estimation with peak delay of different pulse waves

Abstract: In this article, we discuss the validity of noninvasive continuous blood pressure estimation with two different types of peripheral pulse waves. Artery-blocking experiment shows that phase difference of two pulse waves at the same location is well related with blood pressure and blood flow fluctuation. Exercise-recovery experiment resulting from 16 subjects shows that phase difference varies with blood pressure with the correlation from 0.63 to 0.88 when blood pressure changes rapidly. Simulations based on a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Similarly to Kekade et al 2018 [2], we also assessed the studies' reporting of research design (Table 2), and the reported participant demography, i.e., number of participants, age, gender and the distribution of healthy participants and patients (see Sections 3.1-3.4 and Table 3). Many studies presented the participant demographics poorly, or not at all [3][4][5][6][7][8][9][10][11][12]. Rather than excluding these from the tables, we indicate missing information with a "-".…”
Section: Qualitative Synthesismentioning
confidence: 99%
“…Similarly to Kekade et al 2018 [2], we also assessed the studies' reporting of research design (Table 2), and the reported participant demography, i.e., number of participants, age, gender and the distribution of healthy participants and patients (see Sections 3.1-3.4 and Table 3). Many studies presented the participant demographics poorly, or not at all [3][4][5][6][7][8][9][10][11][12]. Rather than excluding these from the tables, we indicate missing information with a "-".…”
Section: Qualitative Synthesismentioning
confidence: 99%
“…The works reported upon in this section include 24/7 systems for ECG monitoring [18][19][20], a preliminary work on person identification aiming toward zero-effort monitoring of cardiovascular diseases [21], three works aiming toward estimating BP continuously without wearing a BP cuff [22][23][24] and work on a bipolar wireless ECG monitor [25,26]. The device was later certified as a medical device, and Reference [27] reported on a number of studies conducted with the device.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Table 6 shows that there are significant shortcomings in the retrieved articles reporting on participant demographics. Five studies [18,19,22,31,32] did not provide any information on the participants' age. Only five of the reported studies [21,25,[28][29][30] and one of the sub-studies in [27] reported on the participants' gender.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…to improve current healthcare systems and citizens quality of life [3]. Multiple sensorization technologies are being investigated and developed towards their application to the monitoring of the health condition, either in a clinical environment or in wearable devices for remote monitoring at the user's home [4,5]: heart rate variability [6], glucose level in the blood [7], blood pressure [4], temperature [8], physical activity [2], pulse oximetry [9], etc. Among these technologies, bioimpedance takes a prominent place, since it allows providing an insight about the internal processes of the body in a noninvasive way [10,11].…”
Section: Introductionmentioning
confidence: 99%